Gambaran Teknik Terapi Aktivitas Kelompok Stimulasi Persepsi pada Pasien Halusinasi di RS Jernaldi Bahar - Riza Riswanda (EDUPEDIA Publisher, 2023)
Objective: This study aims to analyze the technical description of the implementation of Perceptual Stimulation Group Activity Therapy (GAT) in hallucinatory patients.Methods: This study uses a descriptive research method with a quantitative approach. Sampling was done purposively with as many as 73 nurses. Collection and analysis of data using the GAT questionnaire and observation with ordinal scale and univariate analysis.Results: The results showed that the characteristics of nurses who performed GAT on hallucinatory patients based on the majority of nurses aged 26-30 years were 27.4%, the majority of nurses were female 75.3%, the marital status of the majority of nurses were married by 57.5%, and the majority of nurses' education at Ernaldi Bahar Hospital is D3 at 63.0%.Conclusion: Nurses at Ernaldi Bahar Hospital have a GAT level in the category of lacking GAT application techniques in hallucinatory patients. So it is necessary to improve the GAT technique according to the existing Standard Operating Procedure (SOP).